2021
DOI: 10.21926/aeer.2103021
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the COVID-19 Pandemic on the Urban Water Cycle

Abstract: The coronavirus disease 2019 (COVID-19) is a global crisis spreading to all countries. This study explains and documents the first-order effects of the new coronavirus on the urban water cycle. Urban water systems play an important role in public health because people rely so heavily on water services. Findings address short- and long-term changes in climate variables; availability and accessibility of clean water to prevent and control the spread of coronavirus in water-scarce cities; shifts in habits, behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…During major infectious disease outbreaks, the entire urban water cycle system undergoes significant upheaval due to the prolific use of disinfectants and antiviral medications. This metamorphosis potentially results in a substantial influx of pharmaceutical residues and chemical disinfectants into urban water bodies, intensifying the burden of emerging contaminants in aquatic environments . We utilized search index data to model the volume of COVID-19-related queries from November 2022 to May 2023 in China (Figure A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…During major infectious disease outbreaks, the entire urban water cycle system undergoes significant upheaval due to the prolific use of disinfectants and antiviral medications. This metamorphosis potentially results in a substantial influx of pharmaceutical residues and chemical disinfectants into urban water bodies, intensifying the burden of emerging contaminants in aquatic environments . We utilized search index data to model the volume of COVID-19-related queries from November 2022 to May 2023 in China (Figure A).…”
Section: Resultsmentioning
confidence: 99%
“…This metamorphosis potentially results in a substantial influx of pharmaceutical residues and chemical disinfectants into urban water bodies, intensifying the burden of emerging contaminants in aquatic environments. 40 We utilized search index data to model the volume of COVID-19related queries from November 2022 to May 2023 in China (Figure 5A). The infection trends of the pandemic derived from search index are consistent with the trends of COVID-19 infection rates among patients in a flu-like state reported by sentinel hospitals (Figure S14).…”
Section: One-step Detection Of Arg Markers In Urban Watermentioning
confidence: 99%
“…However, this calculation has not included the amount of water needed for surface disinfection activities. Indeed, studies from multiple countries have collectively observed a significant rise in household water demand during the pandemic, especially as people were housebound due to lockdown [6][7][8][9][10][11][12][13][14][15]. Their results further substantiate the vital role that access to uninterrupted water supply plays for an individual's ability to effectively perform the recommended WASH practices [23,37].…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 85%
“…There are several studies that were conducted in different countries during the pandemic which report rising domestic water usage during lockdowns [6][7][8][9][10][11][12][13][14][15]. There are also numerous studies worldwide on how individuals' WASH practices, especially hand washings, have changed during the pandemic [15][16][17][18][19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Long-term hydroclimatic changes may have signi cant impacts on regional water resources [24]. The ndings of this study can help decision-makers to be prepared and react appropriately to changes in regional hydroclimatic conditions of croplands and their potential consequences on water and food resources, particularly under ongoing severe situations like the COVID pandemic [25], water shortages [24,26] and wild res [27]. Longterm hydroclimatic changes may force farmers to change their crops based on the new regional hydroclimate conditions.…”
Section: Discussionmentioning
confidence: 99%